SUBJECT AND AUTHOR INDEXS - IJBE Volume 2 (School of Business, IPB University (SB-IPB), 2016)
SUBJECT INDEX IJBE VOLUME 2access credit, 93acquisition, 177AHP, 61, 82, 165arena simulation,43BMC, 69Bojonegoro, 69brand choice, 208brand image, 208brand positioning, 208bullwhip effect, 43burger buns, 1business synergy and financial reports, 177capital structure, 130cluster, 151coal reserves, 130coffee plantation, 93competitiveness, 82consumer behaviour, 33consumer complaint behavior, 101cooking spices, 1crackers, 1cross sectional analytical, 139crosstab, 101CSI, 12direct selling, 122discriminant analysis, 33economic value added, 130, 187employee motivation, 112employee performance, 112employees, 139EOQ, 23farmer decisions, 93farmer group, 52financial performance evaluation, 187financial performance, 52, 177financial ratio, 187financial report, 187fiva food, 23food crops, 151horticulture, 151imports, 151improved capital structure, 177IPA, 12leading sector, 151life insurance, 165LotteMart, 43main product, 61marketing mix, 33, 165matrix SWOT, 69MPE, 61multiple linear regression, 122muslim clothing, 197Ogun, 139Pangasius fillet, 82Pati, 93pearson correlation, 101perceived value, 208performance suppy chain, 23PLS, 208POQ, 23portfolio analyzing, 1product, 101PT SKP, 122pulp and papers, 187purchase decision, 165purchase intention, 33remuneration, 112re-purchasing decisions, 197sales performance, 122sawmill, 52SCOR, 23sekolah peternakan rakyat, 69SEM, 112SERVQUAL, 12Sido Makmur farmer groups, 93SI-PUHH Online, 12small and medium industries (IKM), 61socio-demographic, 139sport drink, 208stress, 139supply chain, 43SWOT, 82the mix marketing, 197Tobin’s Q, 130trade partnership, 52uleg chili sauce, 1 AUTHOR INDEX IJBE VOLUME 2Achsani, Noer Azam, 177Andati, Trias, 52, 177Andihka, Galih, 208Arkeman, Yandra, 43Baga, Lukman M, 69Cahyanugroho, Aldi, 112Daryanto, Arief, 12David, Ajibade, 139Djoni, 122Fahmi, Idqan, 1Fattah, Muhammad Unggul Abdul, 61Hakim, Dedi Budiman, 187Harianto, 93Hartoyo, 101Homisah, 1Hubeis, Musa, 112Hutagaol, M. Parulian, 93Jaya, Stevana Astra, 93Juanda, Bambang, 52Kirbrandoko, 122, 208Manurung, E. Batara, 130Mukhlis Yusuf, Ahmad, 1Najib, Mukhamad, 165, 197Noor Yuliati, Lilik, 208Nugraha, Artadi, 23Nuryartono, Nunung, 151Oktaviani, Rina, 122Prasetyo, Andrie, 101Primadona, Fitry, 165Qaulan Tsaqiela, Bimahri, 43Ramadhan, Arfin, 82Ridho Nurrochmat, Dodik, 33Rifin, Amzul, 23, 151Rusolono, Teddy, 12Sanim, Bunasor, 43Saptono, Imam Teguh, 130Satria, Arief, 61Setiawan, Indarto, 197Simanjuntak, Mangatas, 12Siregar, Hermanto, 130Suharjo, Budi, 197Sukandar, Dadang, 187Sukardi, 23Sumarwan, Ujang, 33, 165Suprayitno, Gendut, 61Suwandi, Ruddy, 82Syahran, Rinaldi, 187Syarief, Rizal, 69Tinaprila, Netti, 101Trilaksani, Wini, 82Ulfah, Iffatul, 33Wahyudi, Imam, 151Widyatami, Sarah, 52Wijayanto, Hari, 112Wiska, Friesgina, 69Zen, Novian, 177